Biomolecules derived from salivary exosomes encapsulated in chitosan for bone regeneration in alveolar osteitis: A systematic review - Sulistiani, Silvia; Bachtiar, Endang W.; Bachtiar, Boy M. (Narra Sains Indonesia, 2025)
Alveolar osteitis (dry socket) is a common complication after tooth extraction that delays bone healing and causes significant pain. Conventional treatments are largely palliative and do not actively promote regeneration. Salivary exosomes, rich in bioactive molecules, and chitosan, a biocompatible and biodegradable polymer, might offer a promising combined approach for targeted bone regeneration. The aim of this systematic review was to systematically evaluate the regenerative potential of salivary exosomes encapsulated in chitosan for the treatment of alveolar osteitis. The systematic review was conducted following PRISMA guidelines and the PICO framework. Comprehensive searches were performed across PubMed, ScienceDirect, ProQuest, Cochrane Library, and Google Scholar for English-language articles published between 2021 and 2025. Eligible studies included in vitro, in vivo, and preclinical research assessing chitosan-encapsulated salivary exosomes for bone regeneration. Data were extracted on study design, interventions, outcome measures, and therapeutic effects. From 524 retrieved records, 10 full-text articles were assessed, and two met the eligibility criteria. Both studies demonstrated that chitosan encapsulation improved the stability and delivery efficiency of salivary exosomes. Outcomes included increased osteogenic gene expression (ALP, BMP-2, osteocalcin, RUNX2), enhanced angiogenesis, reduced inflammation, and histological evidence of accelerated bone regeneration compared with conventional treatment. In conclusion, current evidence suggests that salivary exosomes encapsulated in chitosan have strong therapeutic potential for alveolar osteitis by promoting osteogenesis, reducing inflammation, and enhancing bone healing. However, further preclinical validation and controlled human trials are required before clinical translation.